DeepGuard: Backdoor Attack Detection and Identification Schemes in Privacy-Preserving Deep Neural Networks. (10th October 2022) - Chen, Congcong; Wei, Lifei; Zhang, Lei; Peng, Ya; Ning, Jianting
Abstract : Deep neural networks (DNNs) have profoundly changed our lifeways in recent years. The cost of training a complicated DNN model is always overwhelming for most users with limited computation and storage resources. Consequently, an increasing number of people are considering to resort to a cloud for an outsourced DNN model training. However, the DNN models training process outsourced to the cloud faces privacy and security issues due to the semi-honest and malicious cloud environments. To preserve the privacy of the data and the parameters in DNN models during the outsourced training and to detect whether the models are injected with backdoors, this paper presents DeepGuard, a framework of privacy-preserving backdoor detection and identification in an outsourced cloud environment for multi-participant computation. In particular, we design a privacy-preserving reverse engineering algorithm for recovering the triggers and detecting the backdoor attacks among three cooperative but non-collusion servers. Moreover, we propose a backdoor identification algorithm adapting to single-label and multi-label attack detection. Finally, extensive experiments on the prevailing datasets such as MNIST, SVHN, and GTSRB confirm the effectiveness and efficiency of backdoor detection and identification in a privacy-preserving DNN model.